Differences of posture on push-off phase between actual speed skating and slide-board training - Xu, D.; Shin, I.; Park, J.; Panday, S. B.; Yang, J.; Kim, K.; Koo, D.; Moon, J. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The slide-board training is a feasible technology to exercise skating during the off-season. While slide-board is much different from ice surface of the actual skating situation, it may distort actual skating posture. The purpose of this study was to analyze the differences in posture during push-off phase between an actual speed skating condition and on slideboard. The result showed that on the slide-board distance between two feet were shorter, so were the rotation angles of both feet, the hip angle was lower during the whole phase, while knee and ankle angles were higher. In conclusion, the restriction of the space on slide-board affected the position and rotation of both stable and push-off feet as well as the joint extension of the stable leg. Hence, the structural design of slide-board needs to be improved to facilitate the extension of knee and ankle in the medial-lateral direction.